Rating Opportunity for Long-Acting Injectable Antipsychotic Initiation Index (ROLIN) - Ifteni, Petru; Petric, Paula-Simina; Teodorescu, Andreea (Frontiers in Psychiatry, 2021)
Background Schizophrenia is a severe psychiatric condition with devastating consequences for the individual's functionality and leading to severe disability. Lack of insight and non-adherence to treatment remain the most important factors in the progression of the disease to chronicity. Despite their proven effectiveness in preventing relapses, reducing morbidity and mortality, long acting injectable antipsychotics (LAIs) are still underused. One of the causes invoked is the lack of guidelines or protocols for initiating LAIs. Objective The aim of this article is to present Rating Opportunity for Long-Acting Injectable Antipsychotic Initiation Index (ROLIN), a clinician-rated index that rates the important factors of the disorder across seven items: age, duration of illness, relapses, antipsychotic treatment response, family support, antipsychotic existing formulation and adherence. Method A retrospective study in which all patients with schizophrenia discharged on oral antipsychotics without LAIs treatment lifetime were evaluated with ROLIN for opportunity for LAIs initiation. Results Of 225 consecutive patients, 126 patients (56%) had a strong indication for initiating LAI (score between 25 and 35). Kolmogorov-Smirnov test was used for checking the normal distribution of values (95% CI for the mean = 9.5781 to 20.4219; 95% CI for the median = 6.5920 to 24.8161; SD = 9.7907; Coefficient of Skewness = 0.0743; Coefficient of Kurtosis = -1.1377). Conclusion This paper proposed an instrument designed to improve treatment in schizophrenia using a simple conceptual model which integrates important predictors of good or poor outcomes. Key words: schizophrenia, antipsychotic, treatment, relapse, outcome, long-acting injectable